New encyclopedia of gardening techniques (Mitchell Beazley, 2008)
Presents best-practice gardening. This book includes steps for planning, pruning, propagating, feeding and watering. It covers various plants including trees, flowers, shrubs, climbers, lawns, vegetables, fruit and herbs. It also shows how to create water features and patios, add lighting; and, includes organic techniques and recycling.